Twentieth-Century Influences on Twenty-First-Century Policing : continued lessons of police reform - Cooper, Jonathon A., 1982- (Lanham: Lexington Books, 2021)
"This newly revised edition includes two new chapters exploring events in policing since 2014, and offers a compelling new direction to improve policing, today"--
Revised edition of Twentieth-century influences on twenty-first-century policing
Includes bibliographical references and index.
Keywords: Police -- United States; Police misconduct -- United States; Police administration -- United States